2000
DOI: 10.1103/physreve.61.733
|View full text |Cite
|
Sign up to set email alerts
|

Short-term forecasting of life-threatening cardiac arrhythmias based on symbolic dynamics and finite-time growth rates

Abstract: Ventricular tachycardia or fibrillation (VT-VF) as fatal cardiac arrhythmias are the main factors triggering sudden cardiac death. The objective of this study is to find early signs of sustained VT-VF in patients with an implanted cardioverter-defibrillator (ICD). These devices are able to safeguard patients by returning their hearts to a normal rhythm via strong defibrillatory shocks; additionally, they store the 1000 beat-to-beat intervals immediately before the onset of a life-threatening arrhythmia. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 33 publications
(8 reference statements)
3
124
0
1
Order By: Relevance
“…Applying our new measures to the HRV data of the pilot study, we were able to detect and quantify the laminar phases before the occurrence of life-threatening cardiac arrhythmia. The differences between VT and the control series were more significant for RQA parameters than for measures used in [Wessel et al, 2000c]. This study also demonstrated the importance of developing sophisticated nonlinear dynamical tools for the analysis (not only) of medical data.…”
Section: Forecasting Of Life-threatening Cardiac Arrhythmiasmentioning
confidence: 74%
See 4 more Smart Citations
“…Applying our new measures to the HRV data of the pilot study, we were able to detect and quantify the laminar phases before the occurrence of life-threatening cardiac arrhythmia. The differences between VT and the control series were more significant for RQA parameters than for measures used in [Wessel et al, 2000c]. This study also demonstrated the importance of developing sophisticated nonlinear dynamical tools for the analysis (not only) of medical data.…”
Section: Forecasting Of Life-threatening Cardiac Arrhythmiasmentioning
confidence: 74%
“…15). The objective of the pilot study in 1998 [Wessel et al, 2000c] was to find early signs of sustained VT in patients with an implanted Fig. 15.…”
Section: Forecasting Of Life-threatening Cardiac Arrhythmiasmentioning
confidence: 99%
See 3 more Smart Citations